Two Symbol Expansion Methods and Their Application to Reversible Data Hiding - Hyoung Joong Kim; Changhee Kang; Sang-Ug Kang (IEEE Access)
In reversible data hiding, image quality preservation and embedding capacity are of utmost importance. This paper proposes two reversible data hiding methods that utilize symbolization of correlations between adjacent pixels: 1) Haar transform representation and 2) pixel concatenation. First, we convert the pixel value into Haar transformed coefficients and use the symbol given by each pair as a domain for the histogram in which the secret data should be embedded. Second, a symbol domain created by concatenating two adjacent pixels was used. Both algorithms exploit the similarity between the neighboring pixels in an image, and the experimental results demonstrate an average PSNR of $64.1dB$ , which is 11.6% higher compared to the original histogram shifting method. The performance of the proposed simple method is comparable to or better than that of more advanced methods that rely on computationally complex prediction techniques.